Numerical Investigation of Fluid In 2D and 3D Lid-Driven Cavity at Different Reynolds Numbers - Maria Margareta Zau Beu; Jiahn Horng Chen (Jurnal IPTEK, 2023)
The lid-driven cavity is an important fluid mechanical system that serves as a benchmark for testing numerical methods and for studying fundamental aspects of incompressible flow in a confined volume. This paper is concerned with the numerical calculation of the LDC on the 2-D and 3-D model. The commercial software ANSYS Fluent was used for the simulation. In these models of the simulated cases, the lid moves in the x-direction. The 2-D solutions for the driven cavity are calculated for 10 ≤ Re ≤ 35,000 with a 501 × 501 and 601 × 601 grid. The driven 3-D cavity is calculated with a 75 × 75 × 75 grid. The steady flow inside the cavity consists of the velocity distributions at different Reynolds numbers. The present numerical results agree well with the literature analytical solutions.